St. Mary's Collegiate Church, Youghal, font, supporting shaft - O'Donovan, Danielle (My University, 2008)
Octagonal baptismal font with hexagonal supporting shafts running from angles of bowl. Moulding comprises frontal mitre flanked at either side by quadrant, hollow chamfer, flat surface, hollow and rear mitre. Rare survival of Decorated font.
Font
Keywords: quadrant; mitre; Architecture, Gothic -- Ireland; Cork (Ireland)--Buildings, structures, etc.; Youghal (Cork, Ireland); Collegiate churches; Baptismal fonts; Late Medieval; roll moldings; moldings, hollow